Every Other Day - Costa, Eveline (Brazil : Sequencia Filmes, 2008)
One day, the filmmaker got off her bus in the southern part of Rio de Janeiro to follow a man whom she saw holding up traffic and doing a risky job that involved pushing a cart made from the body of a fridge down the middle of Niemeyer Avenue. “Every Other Day” is the outcome of their encounter.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films